O8D.8 Severity of carpal tunnel syndrome and manual work: findings from a case-control study. (April 2019) - Mondelli, Mauro; Curti, Stefania; Farioli, Andrea; Aretini, Alessandro; Ginanneschi, Federica; Greco, Giuseppe; Argentino, Antonio; Salce, Caterina; Mattioli, Stefano
Abstract : Objective: Carpal tunnel syndrome (CTS) is a socially relevant condition. This case-control study aims to investigate the association between CTS severity and manual work considering personal anthropometric risk factors as well. Methods: We consecutively enrolled one CTS case for two controls (subjects without clinical and electrophysiological CTS signs) regardless of age and gender who were admitted to the same three outpatient electromyography labs. CTS cases were grouped in three classes of progressive clinical and electrophysiological severity according to two validated five-stage scales. Anthropometric measures and occupational history were collected. Job titles were coded according to the International Standard Classification of Occupations (ISCO 88) by two occupational physicians who were blind to case/control status. Job titles were grouped in two main occupational categories: manual workers and non-manual workers. To assess the association between CTS severity and manual work, ordered logistic regression models (adjusted for age, sex, wrist-palm ratio and waist-stature ratio) were performed. Odds ratios (OR) and 95% confidence intervals (95% CI) were calculated. Results: This case-control study enrolled 370 cases and 747 controls. After the exclusion of retired subjects, subjects older than 65 years and subjects with no information about occupational history, we included 183 cases and 445 controls in the main analysis. For manual workers with respect to non-manual workers, the OR for the electrophysiological severity scale was 2.4 (95%CI 1.5–3.7). Regarding the clinical severity scale, the OR for manual workers compared to non-manual workers were 2.3 (95%CI 1.5–3.7). Conclusion: This study confirms that manual work is an important risk factor for CTS. The association between manual work and CTS severity tends to increase from mild to severe stage of both electrophysiological and clinical scale.